2022
DOI: 10.1161/jaha.122.025931
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Trajectory and Outcome Post Fontan Procedure

Abstract: Background Patients with a single ventricle who experience early life growth failure suffer high morbidity and mortality in the perisurgical period. However, long‐term implications of poor infant growth, as well as associations between body mass index (BMI) and outcome in adulthood, remain unclear. We aimed to model BMI trajectories of patients with a single ventricle undergoing a Fontan procedure to determine trajectory‐based differences in baseline characteristics and long‐term clinical outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…8 In children with a Fontan circulation, above healthy weight range is associated with protection against adverse clinical outcomes. 9,48,49 In contrast, elevated adiposity is associated with poor clinical outcomes in adults living with a Fontan circulation including risk for Fontan circulatory failure and ventricular dysfunction. 8,9 Assessment of an individual's body composition provides a relative indication of the proportion and distribution of body mass compartments-fat mass and fat-free mass.…”
Section: Abnormal Body Compositionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 In children with a Fontan circulation, above healthy weight range is associated with protection against adverse clinical outcomes. 9,48,49 In contrast, elevated adiposity is associated with poor clinical outcomes in adults living with a Fontan circulation including risk for Fontan circulatory failure and ventricular dysfunction. 8,9 Assessment of an individual's body composition provides a relative indication of the proportion and distribution of body mass compartments-fat mass and fat-free mass.…”
Section: Abnormal Body Compositionmentioning
confidence: 99%
“…8,20,49,[67][68][69] Research investigating the weight trajectories of people with a Fontan circulation has demonstrated that adolescence is often the period when weight gain occurs. 48 Concerningly, adiposity tends to accumulate in the trunk or abdominal area. 9,53,70 Given this distribution tendency, there may be merit in measuring waist circumference across all ages to aid in monitoring for excess adiposity although this measurement will be confounded in the presence of ascites.…”
Section: Increased Adipositymentioning
confidence: 99%
See 2 more Smart Citations
“…Compliance was high, with a median training session attendance of 33 (32)(33)(34) out of 36 sessions. In total, 27 patients completed the exercise intervention.…”
Section: Compliance and Drop-outsmentioning
confidence: 99%